IMPLEMENTATION OF MEDIATION IN SHARIA ECONOMIC DISPUTES IN YOGYAKARTA RELIGIOUS COURT - Rivalni - Thamrin; Abdul Mujib (Al-Amwal : Journal of Islamic Economic Law, 2023)
Before bringing a civil matter to a court of first instance, both parties must first make good faith efforts to resolve the issue amicably or through mediation with the help of a third party. Based on data obtained from the Yogyakarta Religious Court, most of the mediation carried out by these mediators was unsuccessful. This research can be classified as field research. The data in this study were obtained from interviews, documentation related to the problem, scientific articles, books, and the official website of the Yogyakarta Religious Court. The research approach is juridical-empirical/juridical-sociological. The results of this study indicate that the settlement of sharia economic problems by mediation at the Yogyakarta Religious Court, in general, can be compared to mediation efforts carried out in other cases, such as divorce or inheritance disputes. Mediated sharia economy is unsuccessful, and the parties only think about mediation, namely the stages of the procedure that must be passed, without understanding the purpose of the mediation process. So it is necessary to provide socialization to the community regarding mediation and improve quality through training or workshops for mediator judges when conducting sharia economic cases by mediation, especially at the Yogyakarta Religious Court.